Association analysis of GHR gene polymorphism with growth traits in sheep - JUNYAN BAI; JINGYUN LI; LIANG WANG; XINLE WANG; ZHIHAO DONG; YU CHEN; YOUBING YANG; XIAOPING JIA; XU WANG; XUEYAN FU; XIANG JI; LONGWEI WANG (Indian Journal of Animal Sciences, 2022)
In this study, polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was employed to investigate the polymorphism of GHR gene and the correlations of polymorphic sites with growth traits. The results showed that GHR detected CC, CD and DD genotypes in the five sheep populations. GHR gene had the highest DD genotype frequencies in Yuxi fatty-tailed sheep, Dorper sheep, Henan large-tailed han sheep, Hu sheep and small-tailed han sheep, being 0.889, 0.784, 0.785, 0.529 and 0.750, respectively. The correlation analysis indicated that GHR gene had significant correlations with chest circumference and abdomen circumference of sheep